Out of pocket expenditures of patients with a chronic condition consulting a primary care provider in Tajikistan: a cross-sectional household survey - Fabienne B. Fischer; Zulfira Mengliboeva; Gulzira Karimova; Nasrullo Abdujabarov; Helen Prytherch; Kaspar Wyss (BMC, 2020)
Abstract Background Within its reform efforts, the Government of Tajikistan is embracing the essential role of primary health care (PHC) in decreasing out of pocket (OOP) expenditures and increasing equity in access to health services. In the light of the increasing burden of disease relating to chronic conditions, we investigated OOP expenditures of patients with chronic conditions within a PHC setting; and if and how those expenditures are impacted by several interventions currently being implemented within Tajikistan. Methods A cross-sectional survey among 1600 adult patients who had visited a PHC facility was conducted. The data obtained through interviews were descriptively analysed, and logistic regressions and gamma generalized linear models were performed. Results The total OOP expenditures related to a patient's last visit to the PHC facility were 17.2 USD for those with chronic conditions and 13.9 USD for those visiting due to an acute condition. Adjustment for potential confounders reduced the discrepancy from 3.3 USD to 0.5 USD. This convergence of costs was only observed in districts covered by the Basic Benefit Package (BBP), a governmental pilot project, aiming to standardise exemptions for payment and formal co-payments for health care services. Hence, we found the BBP to have a protective impact for patients with chronic conditions. However, considering the demographics of these patients (older in age, with greater dependency on pensions and social aid, and lower socio-economic status) in combination with the 40% higher utilisation rate of PHC and the high rate of onward referrals to specialists; it is clear that patients with chronic conditions continue to face substantial long-term costs and disadvantages. Conclusions After accounting for confounders, patients with chronic and acute conditions faced similar costs related to a single visit to a PHC facility in districts covered by the BBP. However, greater efforts are required to ensure that citizens are well informed about their rights to health care, the BBP and the services that should be provided at no cost at the point of delivery. Moreover, the needs of patients with chronic conditions warrant a more integrative approach that takes long-term expenditures and services beyond the level of PHC into account.